Prevalence and risk factors for subclinical atherosclerosis amongst adults living with HIV in University of Abuja Teaching Hospital, Gwagwalada - Adedokun, Taiwo A.; Kwaghe, Vivian G.; Adedokun, Oluwasanmi; Badru, Titilope; Odili, Augustine N.; Alfa, Jacob; Kolade-Yunusa, Hadijat O.; Ojji, Dike B. (Frontiers in Reproductive Health, 2023)
Background Subclinical atherosclerosis characterizes cardiovascular diseases (CVD), and Human Immunodeficiency Virus (HIV) infection and antiretroviral therapy (ART) are identified risk factors for atherosclerosis. Meanwhile, data on HIV and atherosclerosis in Nigeria are limited. Objectives We sought to estimate the prevalence of subclinical atherosclerosis and associated risk factors amongst adult persons living with HIV/AIDS (PLHIV) enrolled at University of Abuja Teaching Hospital, Gwagwalada, Abuja (UATH). Methods This was a cross-sectional study of 277 consecutively selected PLHIV ≥18 years enrolled for HIV care and treatment at UATH. Pretested structured questionnaire was used to collect data from consenting ART-experienced and ART-naïve patients on risk factors of atherosclerosis. Carotid intima media thickness (CIMT) ≥0.71 mm as measured by Doppler ultrasonography was used to identify patients with sub-clinical atherosclerosis. Two logistic regression models with (Model-A) and without (Model-B) traditional risk factors were fitted to identify risk factors of subclinical atherosclerosis. Results Participants' mean age was 39.44 ± 10.71 years with female preponderance (64.26%). Overall prevalence of subclinical atherosclerosis was 43.32% (62.25% in ART-experienced). Model-A identified male sex [AOR 4.33(1.74–10.76), p = 0.002], advancing age [30–39 years AOR 5.95(1.31–26.96), p = 0.021]; ≥40 years AOR 19.51(4.30–88.56), p ≤ 0.001), advancing HIV infection [≥WHO stage II AOR 4.19(1.11–15.92), p = 0.035], hypercholesterolemia [AOR 3.88(1.47–10.25), p ≤ 0.001] and ≥5 year duration on ART [AOR 9.05(3.16–25.92), p ≤ 0.001] as risk factors of subclinical atherosclerosis. In Model-B (excluding traditional risk factors) on the other hand, advancing HIV infection [≥WHO stage II AOR 3.93(1.19–13.042), p = 0.025] and duration on ART [≥5 years AOR 11.43(4.62–28.29), p = 0.001] were found as risk factors of subclinical atherosclerosis. Conclusion Subclinical atherosclerosis was higher in ART-experienced patients, and this was irrespective of presence or absence of traditional risk factors. And advancing HIV disease and duration on ART were found as significant risk factors for subclinical atherosclerosis. We therefore recommend routine CVD risk screening in PLHIV.